Analysis of Organizational Communication Strategies in Tourism Development: A Case Study of the Indonesia Tourism Development Corporation (ITDC) - Made Sera Septiani; Ni Putu Yumita Arie Puteri; Ni Wayan Gita Sadhana Savitri; Ni Luh Kadek Laksmi Wulandani (Pubfine Media Group, 2026)
Introduction: The Indonesia Tourism Development Corporation (ITDC) is a state-owned enterprise (SOE) that plays a strategic role in the development and management of integrated tourism destinations in Indonesia. The successful development of tourism areas, such as The Nusa Dua, The Mandalika, and The Golo Mori, is determined not only by physical infrastructure development but also by effective communication strategies that foster synergy between the organization and its various stakeholders. Therefore, analyzing ITDC's communication strategies is essential to understanding how organizational communication supports sustainable tourism development. Methods: This research employed a qualitative descriptive approach. Data were collected through observations, in-depth interviews with the Vice President of Marketing and Relations of the Nusa Dua ITDC, documentation, and a literature review. Data were analyzed using the stages of data reduction, data display, and conclusion drawing through a descriptive analysis approach. Results: The findings reveal that ITDC implements an integrated organizational communication strategy through both internal and external communication to support sustainable tourism destination development. Internal communication is strengthened through open and transparent information sharing, multiple communication channels, and employee communication skills development, enhancing coordination and collaboration across the organization. External communication focuses on building long-term relationships with government agencies, local communities, investors, business partners, the media, and tourists through direct engagement, digital media, and corporate branding. Furthermore, ITDC utilizes integrated information systems and digital platforms, including ERP, HRIS, e-Office, its corporate website, and social media, to improve communication efficiency, stakeholder engagement, corporate transparency, and destination promotion. Conclusion: ITDC's integrated organizational communication strategy, supported by digital technology and stakeholder-oriented communication, plays a significant role in strengthening organizational effectiveness and fostering collaboration in tourism destination development. These strategies contribute to enhancing the competitiveness and sustainability of Indonesia's integrated tourism destinations.